2002
DOI: 10.1093/ajcn/76.3.511
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protein source on resistive-training-induced changes in body composition and muscle size in older men

Abstract: These data suggest that increases in muscle strength and size were not influenced by the predominant source of protein consumed by older men with adequate total protein intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
106
1
13

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(127 citation statements)
references
References 29 publications
7
106
1
13
Order By: Relevance
“…It is not immediately clear as to why meat proteins are superior to plant-based proteins in the stimulation of MPS, but it is not likely something driven by amino acid content (i.e., PDCAAS). It is noted, that in a follow-up study to the original observations Campbell et al (1999) and Haub, Wells, Tarnopolsky, and Campbell (2002) found no statistical difference in muscle mass gain between men who consumed meat-containing diets and men in lacto-ovo-vegetarian diets and performed resistance training despite a 43% greater increase in the muscle fiber area in the meat-consuming subjects.…”
Section: Dose-response Of Mpsmentioning
confidence: 84%
“…It is not immediately clear as to why meat proteins are superior to plant-based proteins in the stimulation of MPS, but it is not likely something driven by amino acid content (i.e., PDCAAS). It is noted, that in a follow-up study to the original observations Campbell et al (1999) and Haub, Wells, Tarnopolsky, and Campbell (2002) found no statistical difference in muscle mass gain between men who consumed meat-containing diets and men in lacto-ovo-vegetarian diets and performed resistance training despite a 43% greater increase in the muscle fiber area in the meat-consuming subjects.…”
Section: Dose-response Of Mpsmentioning
confidence: 84%
“…In accordance, when habitual dietary protein intake is standardized at 0.9 g⅐kg Ϫ1 ⅐day Ϫ1 , exercise-induced increases in muscle mass become apparent, and a further increase in protein intake does not seem to have any additional effect (61). The latter might explain why most studies fail to observe any additional benefit of nutritional cointervention on the skeletal muscle adaptive response to prolonged resistance-type exercise training in the elderly (22,40,41,43,47,54,59,61,86,118,129). However, the absence of any benefits of nutritional cointervention may well be attributed to a less than optimal timing of amino acid and/or protein supplementation that was applied in these studies.…”
Section: Exercise Training In the Elderlymentioning
confidence: 88%
“…Proteins: animal and vegetal sources When the total protein intake is adequate, the source of protein consumed (vegetal or animal) does not influence muscle strength and size [36] Increases in muscle strength and size were not influenced by the predominant source of protein consumed by older men with adequate total protein intake Branched chain amino acids (BCAAs), It is recommended to have an adequate daily leucine supplementation (3 g/day)…”
Section: Discussionmentioning
confidence: 99%